Foreword - Velarde Molina, Dr. Jehovanni Fabricio (International Journal of Interactive Multimedia and Artificial Intelligence, 2022)
This time, in the Special Issue on Artificial Intelligence in Economics, Finance and Business, we present a series of publications focused on artificial intelligence and finance. This compilation of research will bring new information to researchers in different disciplines, and at the same time, it will be an ideal space to present studies that have an international scope. UNIR, dedicated to the training of professionals in different academic programs, through its journal is consolidating a culture of research and expanding the knowledge that contributes to an excellent education. For this reason, we consider the dissemination of scientific articles essential, since this guarantees the transfer of results, in addition to the conclusions of high-impact research. Currently the world is going through a complicated scenario, a fluctuating economy and problems in health services that require immediate attention; in this sense, science and knowledge management open space to opportunities in search of medium and long-term solutions. It is a great honor to present this issue of the International Journal of Interactive Multimedia and Artificial Intelligence, whose contribution to the knowledge society is invaluable.